Antioxidants and Anti-Inflammatory Effects in Neurodegenerative Diseases (NDs) - Michela Campolo; Irene Paterniti (MDPI AG, 2022)
Neurodegenerative diseases (NDs) are the most common chronic neurological diseases associated with age, and they have a strong impact on the patient's quality of life [...]